Adverse childhood experiences (ACEs) and later-life depression: perceived social support as a potential protective factor - Patricia M Kearney; Carol Sinnott; Darren Dahly; E Von Cheong (BMJ Open)
Objective To investigate associations between adverse childhood experiences (ACEs) and later-life depressive symptoms; and to explore whether perceived social support (PSS) moderates these.Method We analysed baseline data from the Mitchelstown (Ireland) 2010–2011 cohort of 2047 men and women aged 50–69 years. Self-reported measures included ACEs (Centre for Disease Control ACE questionnaire), PSS (Oslo Social Support Scale) and depressive symptoms (CES-D). The primary exposure was self-report of at least one ACE. We also investigated the effects of ACE exposure by ACE scores and ACE subtypes abuse, neglect and household dysfunction. Associations between each of these exposures and depressive symptoms were estimated using logistic regression, adjusted for socio-demographic factors. We tested whether the estimated associations varied across levels of PSS (poor, moderate and strong).Results 23.7% of participants reported at least one ACE (95% CI 21.9% to 25.6%). ACE exposures (overall, subtype or ACE scores) were associated with a higher odds of depressive symptoms, but only among individuals with poor PSS. Exposure to any ACE (vs none) was associated with almost three times the odds of depressive symptoms (adjusted OR 2.85; 95% CI 1.64 to 4.95) among individuals reporting poor PSS, while among those reporting moderate and strong PSS, the adjusted ORs were 2.21 (95% CI 1.52 to 3.22) and 1.39 (95% CI 0.85 to 2.29), respectively. This pattern of results was similar when exposures were based on ACE subtype and ACE scores, though the interaction was clearly strongest among those reporting abuse.Conclusions ACEs are common among older adults in Ireland and are associated with higher odds of later-life depressive symptoms, particularly among those with poor PSS. Interventions that enhance social support, or possibly perceptions of social support, may help reduce the burden of depression in older populations with ACE exposure, particularly in those reporting abuse.